The Analysis of Code Mixing Used by Junior High School Students - Retno Apridhayati (English Language Teaching Prima Journal (ELT), 2019)
Abstract This objective of the study was to investigate and analyze the types of code mixing used by Junior High School students. The study used descriptive qualitative method. Each sentence from the students conversation was carefully identified to determine its code mixing type according to Hoffman’s theory (1991). The data of the study is utterances which code mixing is included in it. The technique of the data collections used is documantary technique. It is found that there were three types of code mixing used by Junior High School students according to Hoffman theory namely : (1) intra-sentential code-mixing, (2) intra-lexical code-mixing, (3) code-mixing involving change of pronunciation. According to Hoffman theory there are four reasons of using code mixing but in this study it was found that the dominant reason is “If someone is exposed to mixed input, s/he will often respond with mixed production.”